2014
DOI: 10.4161/hv.27816
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage and factors affecting adherence to influenza vaccination among patients with diabetes in Taiwan

Abstract: The purpose of this study was to investigate influenza vaccination coverage and the factors influencing acceptance of influenza vaccination among patients with diabetes in Taiwan using the Health Belief Model (HBM). From January 1 to February 28, 2012, 700 patients with diabetes who visited National Cheng Kung University Hospital were invited to participate in the study. A total of 691 (99%) patients with diabetes were enrolled in the study. The mean age of the subjects was 64.7 years (SD = 10.7). The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
4
21
0
1
Order By: Relevance
“…Although multivariate analysis in our study confirmed that awareness and treatment rates of diabetes was significantly associated with influenza vaccination in diabetic patients under 65 years, univariate analysis results were similar to those of previous studies. Influenza vaccination rate was higher in women aged both under 65 years and older than 65 years, as shown in previous studies [ 25 35 ]. In general, females have a tendency to prefer healthy lifestyle.…”
Section: Discussionsupporting
confidence: 77%
“…Although multivariate analysis in our study confirmed that awareness and treatment rates of diabetes was significantly associated with influenza vaccination in diabetic patients under 65 years, univariate analysis results were similar to those of previous studies. Influenza vaccination rate was higher in women aged both under 65 years and older than 65 years, as shown in previous studies [ 25 35 ]. In general, females have a tendency to prefer healthy lifestyle.…”
Section: Discussionsupporting
confidence: 77%
“…Most sociodemographic factors present a mixed picture of results. As such, higher age was reported as a barrier to vaccine uptake (HCP 5/117 [ 53 , 54 , 89 , 285 , 331 ]; Chronic 3/45 [ 291 , 431 , 445 ], Children 3/18 [ 97 , 402 , 446 ]; Public 8/191 [ 72 , 108 , 224 , 309 , 396 , 447 449 ]) but also as a promotor (HCP 30/117 [ 45 , 46 , 51 , 55 , 75 , 91 , 131 , 133 , 274 , 280 , 289 , 323 , 374 , 450 – 465 ]; Pregnant 3/35 [ 57 , 297 , 324 ]; Chronic 21/45 [ 95 , 238 , 290 , 294 , 321 , 325 , 349 354 , 370 372 , 386 388 , 399 , 466 468 ]; Children 2/18 [ 119 ,…”
Section: Resultsmentioning
confidence: 99%
“…More evidence is found regarding the compliance of the chronic patients; the literature shows that chronic patients tend to be skeptical about the importance of vaccination and that they underestimate the consequences of the disease, with subsequently low vaccination coverage . [13][14][15]20 All studies agree that a careful and scrupulous information and education of the patient is necessary to increase adherence to vaccination; [13][14][15]20 the hospital setting, that is the setting of our immunization program, seems to be an ideal scenario for the vaccine promotion. The studies that have dealt with the issue of strategies to increase vaccine compliance assure that patients who receive preventive care are more likely to get their influenza shot than those who do not receive; furthermore, the health professionals involved in the care of patients affected by chronic conditions should encourage patients and family members to get immunized to prevent infectious diseases or minimize the risk.…”
Section: Discussionmentioning
confidence: 99%